أثر استراتيجية المكعب في تحصيل طلبة الصف السابع الأساسي في مبحث الرياضيات في محافظة قلقيلية واتجاهاتهم نحو تعلمها - صالحة، سهيل حسين; شواهنة، آلاء; بركات، على (جامعة النجاح الوطنية, 2017)
This study aimed to determine the effect of the cubing strategy in the achievement of the basic seventh grade students in mathematics in Qalqilya governorate, the researchers adopted the quasi experimental methodology in its application in the seventh grade female students. The study reached that there is statistically significant difference between student sand attitudes achievement in the experimental and control group due to the teaching method (traditional, cubing strategy), the results were in favor of the experimental group .There is a statistically significant association at p between students’ achievement and attitudes toward learning mathematics for the female students in the seventh grade. Based on the study findings, the researchers recommend training educational supervisros and teachers on using modern methods in teaching as cubing strategy, encouring teachers to apply cubing strategy in other topics as Algebra and Measurement, and also in other subjects like Science and Geography.
هدفت الدراسة إلى معرفة أثر تدريس وحدة الهندسة باستخدام استراتيجية المكعب في التحصيل والاتجاه نحو تعلّم الرياضيات لدى طالبات الصف السابع الأساسي في محافظة قلقيلية، واستخدم الباحثون المنهج التجريبي بتصميم شبه تجريبي، من خلال تطبيق الدراسة على عينة (50) طالبة من طالبات الصف السابع الأساسي، وبلغ مجتمع الدراسة (2198) طالب وطالبة وقد توصل الباحثون إلى وجود فرق ذي دلالة إحصائية بين متوسطي التحصيل والاتجاهات بين طلاب المجموعة التجريبية والمجموعة الضابطة ولصالح المجموعة التجريبية التي درست باستخدام استراتيجية المكعب، ووجود علاقة ذات دلالة إحصائية بين التحصيل الدراسي والاتجاهات نحو تعلّم الرياضيات لطالبات الصف السابع الأساسي، وبناءا على نتائج الدراسة أوصى الباحثون بعدد من التوصيات منها تدريب المشرفين التربويين والمعلمين على استخدام الطرق الحديثة في التدريس، والتي من ضمنها استراتيجية المكعب، بربط الرياضيات بالحياة العلمية والخبرات اليومية. وتشجيع المعلمين لتطبيق استراتيجية المكعب في مواضيع أخرى مثل الجبر، والقياس، وأيضا في مباحث أخرى كالعلوم، والجغرافيا.
Keywords: الاستراتيجيات التربوية -- طلاب المرحلة الاساسية -- التحصيل الدراسى -- تدريس الرياضيات -- الاردن